2006
DOI: 10.1016/j.amjhyper.2006.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Masked Hypertension and Target Organ Damage in Treated Hypertensive Patients

Abstract: Our findings indicate that masked hypertension is associated with advanced target organ damage in treated hypertensive patients, comparable to that in cases of sustained hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 24 publications
3
50
2
1
Order By: Relevance
“…Nocturnal dipping was larger in white coat hypertensives opposed to earlier studies 25 and was similar in masked and sustained hypertensives. 26 The first morning BP readings were higher in the MH than in the WCH group and comparable to the SH group, adding another risk factor related to target organ damage and cardiovascular morbidity. 27 In line with earlier reports, MH was related to physical training, higher educational level and higher sense of responsibilities at work than at home, which can be regarded as greater reactivity to daily stressors that might increase daytime BP.…”
Section: Discussionmentioning
confidence: 84%
“…Nocturnal dipping was larger in white coat hypertensives opposed to earlier studies 25 and was similar in masked and sustained hypertensives. 26 The first morning BP readings were higher in the MH than in the WCH group and comparable to the SH group, adding another risk factor related to target organ damage and cardiovascular morbidity. 27 In line with earlier reports, MH was related to physical training, higher educational level and higher sense of responsibilities at work than at home, which can be regarded as greater reactivity to daily stressors that might increase daytime BP.…”
Section: Discussionmentioning
confidence: 84%
“…24 In addition, our recent study showed that masked hypertension was associated with advanced target organ damage in treated hypertensive patients, comparable to that in cases of sustained hypertension. 25 Furthermore, prospective studies have revealed that a high ambulatory or home BP is a powerful predictor for cardiovascular morbidity and mortality in the general population and treated hypertensive patients even when their office BP is normal or well controlled. 10,11,[26][27][28] As for the association between LV geometry and cardiovascular prognosis, it was reported that hypertensive patients with concentric hypertrophy among four LV geometric patterns had the highest incidence of cardiovascular events and death.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular mass index, carotid maximal intimamedia thickness, and urinary albumin level were higher in persons with masked hypertension than in persons with controlled hypertension and similar to those with sustained hypertension (7). A meta-analysis of seven studies including 11,502 persons, mean age 63 years, showed at 8.0-year follow-up that compared to normotensive persons, persons with masked hypertension had a 2.0 times increase in first cardiovascular events, and persons with sustained hypertension had a 2.28 times increase in first cardiovascular events (8).…”
mentioning
confidence: 96%
“…Masked hypertension was diagnosed by ambulatory blood pressure monitoring in 14% of persons and by home blood pressure monitoring by 11% of persons (6). It may be reasonable to screen for masked hypertension with ambulatory blood pressure monitoring or with home blood pressure monitoring if the office systolic blood pressure is 120 to 129 mmHg or if the office diastolic blood pressure is 75 to 79 mmHg (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%